Macroscopic‐Oriented Gold Nanorods in Polyvinyl Alcohol Films for Polarization‐Dependent Multicolor Displays. Issue 11 (30th March 2018) - Dai, Liwei; Lu, Xuefei; Song, Liping; Huang, Youju; Liu, Baoqing; Zhang, Lei; Zhang, Jiawei; Wu, Si; Chen, Tao
Abstract: Due to their abundant optical colors, durable color generation, and high refreshing rate, smart chromic nanomaterials (SCNMs) have been employed in various applications. However, most SCNMs often require multicomponent materials, precise morphology control, and complicated modulation to realize multicolor changes, which limits their widely practical applications. In the present study, a simple and effective strategy is demonstrated to achieve the flexible and cost‐effective multicolor gold nanorods (Au NRs)/polymer hybrid film, by tuning macroscopic‐oriented Au NRs in films and a synergy of polarization‐dependent surface plasmon resonance. Au NRs are first functionalized with methoxypoly(ethylene glycol)thiol to improve the compatibility, ensuring Au NRs can be homogenously dispersed in the polyvinyl alcohol (PVA) matrix with high particle density. The macroscopic‐oriented alignment of Au NRs can be achieved by the elongation of the PVA polymer molecular chains. Under different polarized excitation directions, the same strip of the hybrid film exhibits various colors including red, orange, yellow, and green. Therefore, the strategy provides a simple and powerful approach to achieve macroscopic‐oriented anisotropic nanoparticles in the polymer matrix, and the resultant hybrid films are promising in various practical applications, such as color displays, optical devices, and plasmonic biosensors. Abstract : The macroscopic‐oriented gold nanorods (Au NRs) alignment displays the synergistic effect of an individual Au NR plasmonic property, making the Au NRs/polyvinyl alcohol (PVA) hybrid film as a smart polarization‐dependent color displays. Under the different polarized excitation directions, the same strip of the Au NRs/PVA hybrid film exhibit various plasmonic colors including red, orange, yellow, and green and would be promising in various smart optical devices.